UMP wins 14 gold, 10 silver medals for innovative research tools - Siti Nur Azwin, Zulkapri (The New Straits Times Press (M) Bhd., 2022)
KUANTAN: An innovation to boost the extraction of agarwood oil was among the outstanding products that saw Universiti Malaysia Pahang (UMP) walk away with 14 gold medals at the International Invention, Innovation and Technology Exhibition (ITEX) 2022 at the Kuala Lumpur Convention Centre recently.